Experimental Study on Grouting Diffusion Law of Tunnel Secondary Lining Cracks Based on Different Slurry Viscosities - Bin Zhang; Peng Liu; Yi Wu; Liming Wu; Chen Li; Shiyang Liu; Yuanfu Zhou (Applied Sciences)
To investigate the diffusion law of ultrafine cement slurry (UCS) with different water–cement ratios in tunnel second lining cracks during grouting, the grouting of ultrafine cement slurry with different water–cement ratios was carried out by experimental and theoretical analysis methods in this study. Through the collection and data analysis grouting experiment of the diffusion time history, the diffusion morphological characteristics based on different slurry viscosities were obtained, which were divided into three grouting diffusion patterns: circular diffusion zone, excessive diffusion zone, and elliptical diffusion zone. Furthermore, the spatiotemporal variation rules of the diffusion radius of ultrafine cement slurry with different water–cement ratios in tunnel secondary lining cracks were obtained as well. By analyzing the diffusion radius values under different water–cement ratios in each direction of x+, x−, y+, and y−, the critical water–cement ratios ξ were found to be 0.8, which affected the diffusion radius value in the vertical upward y+ direction. Meanwhile, when the grouting was completed, the maximum diffusion radius of the ultrafine cement slurry was obtained using different water–cement ratios in each direction. Moreover, the grouting diffusion equation of tunnel secondary lining cracks based on ultrafine cement slurry with different water–cement ratios is established. The research results can accurately predict the grouting diffusion pattern and diffusion radius in tunnel second lining cracks with different water–cement ratios of ultrafine cement slurry.